The effect of sawdust on shear strength properties of peat soil - Nur Syazana , Norruddin (2013)
Peat soil is an extremely formed of soft soil that always considered problematic by the numerous engineers. In the construction field, peat soil is not being the engineer's choice due to its properties that is low in shear strength and high compressibility. This weakness gives difficulties to engineer to develop infrastructures and facilities due to the limited lands in Malaysia. An appropriate soil improvement is needed. Stabilizing the peat soil is the most effective way to overcome the drawback of this issue. This paper presents a study on the effect of sawdust on shear strength properties of peat soil that has been conducted for sampling area at Kampung Tanah Puteh in area of Pekan, Pahang. A total of 15 samples of peat soil with various mixes proportion of sawdust varies from 0%, 1.0%, were analyzed by laboratory testing that subjected to normal stress of 136.2kPa, 272.5kPa and 408.8kPa at each of the proportion. The direct shear test was performed to determine the parameters of shear strength which are cohesion and angle of shear resistance and determination of the optimum mix of sawdust with peat soil which gives the maximum shear strength. The study revealed that by adding sawdust at exact 1.5%, 2.0% and 2.5% value can give the maximum value of shear strength. The shear strength parameter which is cohesion is inversely proportional to the angle of shear resistance. The optimum mix for peat soil was at 1.0% of sawdust.